Exhaustive CoMFA and CoMSIA analyses around different chemical entities: a ligand-based study exploring the affinity and selectivity profiles of 5-HT1A ligands - Sara Guariento; Silvia Franchini; Michele Tonelli; Paola Fossa; Claudia Sorbi; Elena Cichero; Livio Brasili (Taylor & Francis Group, 2017)
The 5-hydroxytryptamine (5-HT1A) receptors represent an attractive target in drug discovery. In particular, 5-HT1A agonists and partial agonists are deeply investigated for their potential role in the treatment of anxiety, depression, ischaemic brain disorder and more recently, of pain. On the other hand, 5-HT1A antagonists have been revealed promising compounds in cognition disorders and, lately, in cancer. Thus, the discovery of 5HT1A ligands is nowadays an appealing research activity in medicinal chemistry. In this work, Comparative Molecular Fields Analysis (CoMFA) and Comparative Molecular Similarity Index Analysis (CoMSIA) were applied on an in-house library of 5-HT1A ligands bearing different chemical scaffolds in order to elucidate their affinity and selectivity for the target. Following this procedure, a number of structural modifications have been drawn for the development of much more effective 5-HT1AR ligands.